O Pão (1892-1896): amor e trabalho nas fornadas da sociedade artístico-literária - Padaria espiritual: o engajamento da irreverência cearense em uma proposta lúdico-literária - Melo, Maria Elizabeth Cosmo (2021)
This dissertation talks about the importance of idleness as a productive activity capable of performing the potencial inherent in the human being, according to writings in the newspaper O Pão, edited between 1892 and 1896. The authors of this newspaper, the “baker-writers” called themselves men of the arts and the letters and created the group called Padaria Espitirual aiming to shake the provincial environment full of retoric of Fortaleza in the end of the XIX century, and ambitioned to resonate beyond Ceará. The proposal was to take the bread of the spirit to everyone in general, and for that, went through squares and streets of the city and the interior of the state, mixing and adding up with everyone else, using a playful and literary proposal. The research supports itself in evidences found on the paper O Pão, from the imanent analysis of the sources. In that sense, the paper was cataloged and its categories were classified according to its specificities, spreading the writing subjectivities along the research, uniting the various genres of text and literary styles. In that way, promoting an interdisciplinary discussion. We understand that the group proposed themselves with a didactic mission because, at the same time they were loud about social and political issues experienced in an inhumane environment, they sought to rescue the spirit and the importance of love and friendship relations, that were being lost. Unwillingly or not, they had to board the modernity train, and wrapped around the seduction of new things, they longed for idealizing a world and a type of work in which they could find themselves as individuals